A global review of the impact on women from men's alcohol drinking: the need for responding with a gendered lens - Ingrid M. Wilson; Bree Willoughby; Amany Tanyos; Kathryn Graham; Mary Walker; Anne-Marie Laslett; Leane Ramsoomar (Taylor & Francis Group, 2024)
Background Global evidence shows that men's harmful alcohol use contributes to intimate partner violence (IPV) and other harms. Yet, interventions that target alcohol-related harms to women are scarce. Quantitative analyses demonstrate links with physical and verbal aggression; however, the specific harms to women from men's drinking have not been well articulated, particularly from an international perspective. Aim To document the breadth and nature of harms and impact of men's drinking on women. Methods A narrative review, using inductive analysis, was conducted of peer-reviewed qualitative studies that: (a) focused on alcohol (men's drinking), (b) featured women as primary victims, (c) encompassed direct/indirect harms, and (d) explicitly featured alcohol in the qualitative results. Papers were selected following a non-time-limited systematic search of key scholarly databases. Results Thirty papers were included in this review. The majority of studies were conducted in low- to middle-income countries. The harms in the studies were collated and organised under three main themes: (i) harmful alcohol-related actions by men (e.g. violence, sexual coercion, economic abuse), (ii) impact on women (e.g. physical and mental health harm, relationship functioning, social harm), and (iii) how partner alcohol use was framed by women in the studies. Conclusion Men's drinking results in a multitude of direct, indirect and hidden harms to women that are cumulative, intersecting and entrench women's disempowerment. An explicit gendered lens is needed in prevention efforts to target men's drinking and the impact on women, to improve health and social outcomes for women worldwide.